2020
DOI: 10.30564/jasr.v3i2.2010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Nexus between Climate Change, the Shift in Land Use toward Cashew Production and Rural Food Security in Ghana; the Experiences of Farmers in the Transition Zone of Ghana

Abstract: This study summarises the findings from a study investigating rural small-holding farmers’ experiences on the shift from food crop to cashew in the forest/savanna transitional agro-ecological zone of Ghana and its impact on rural food security. Using a mix method approach, the study sampled the views of 400 farmers from 9 farming communities in the Wenchi Municipality of Ghana via questionnaire and semi-structured interview and collated statistical data on crop production to trace the nexus between climate cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…Thus, implying that increases in human capital accumulation result in poverty reduction. The relationship observed between human capital and poverty is consistent with studies by Addison et al(2016) that investment in human capital is viewed as a panacea for poverty reduction.…”
Section: Association Between Human Capital Economic Growth and Povertysupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, implying that increases in human capital accumulation result in poverty reduction. The relationship observed between human capital and poverty is consistent with studies by Addison et al(2016) that investment in human capital is viewed as a panacea for poverty reduction.…”
Section: Association Between Human Capital Economic Growth and Povertysupporting
confidence: 88%
“…There is an extensive research literature on the impact of human capital on economic growth and poverty). Studies by Abbas (2001), Mattalia (2012), Addison et al (2016), Adekoya (2018), Pavlova (2018), Picatoste et al, (2018), Ahmad and Khan, (2019), Olopade et al (2019) and Collin and Weil (2020), found that investment in human capital has a correlative effect on economic growth and poverty reduction. Adekoya's (2018) investigation on the impact of human capital development on poverty alleviation in Nigeria found that investment in education and health by the Nigerian federal government resulted in a reduction of poverty.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…However, Southern Africa, some regions of East and North Africa have witnessed a rise in precipitation. In the same vein, rise in air temperatures leading to higher rates of evapotranspiration, which result in drier soil conditions [14] have been reported. It is on record that between 2001 and 2017, Zambia has experienced constant rise in evaporative stress.…”
Section: Climate Of Africa: Past and Presentmentioning
confidence: 63%
“…According to the study, even places witnessing a rise in rainfall regime, there is a probability that worsening water stress would impact crop system negatively neutralising the gains achieved [17] . The amount of the temperature increase, and the changes in cloud cover, depending on timing of rainfall, larger areas are likely to experience water availability both in streams and in the soil, but high air temperatures, however, would lead to water loss in the soil through vegetation in the process of evaporation [14] . Atmospheric temperatures and rainfall alteration have significant repercussion on food system and security on the African sub-region [26,27] .…”
Section: Expected Changes In Precipitation For African Sub-regionmentioning
confidence: 99%
“…22,23 This had made a lot of food crop producers to shift to the production of cash crop (cashew) which had been identified by the farmers to be somewhat resistant to the erratic rainfall. 24 Again, in Ghana, climate change is projected to affect crop production, food security, water security, energy supply especially in the northern part of the country. 25,26 From Figure 1…”
Section: Impacts Of Changes In Precipitation and Temperature On African Agriculturementioning
confidence: 99%